The best prominent scholars of The Arabic language in Damascus through "The book Al-daris fi tarikh Al-Madaris" by Al-Nuaimi Died in 927 AH -1521 AD - Al-Amoush, Anas Nayef (Journal of Humanities & Social Sciences, 2021)
This study aimed to focus on the light of The Arabic language and its scholars through the book " Al_daris fi tarikh Al_Madaris " by Abdul Qadir Al_Nuaimi, which is considered the first one of books that we received, and that chronicles to schools of Damascus, as this study also included on the highlighting scholars of the Arabic language in Damascus and it was the most important centers which the science of language. Its scholars contributed to preserve The Arabic language and its safety. As well as, there were many famous scholars appeared in this wide field who played a big role that contributed to its development and prosperity.
Keywords: The student in the history of schools; Al-Nuaimi; Damascus; education; the Mamluk era; the Arabic language